APPLICATION OF NEURAL NETWORK IN MONITORING THE THERMAL STATE OF BIOLOGICAL TISSUE IN THE WELDING ZONE - Solovyov, V. G.; Lankin, Yu. M.; Romanova, I. Yu. (Medical Informatics and Engineering, 2024)
Background. The article discusses modern methods of regulating the welding process of soft biological tissues, based on the measurement of electrical parameters of high-frequency current and control of welding time. However, these methods do not consider input parameters such as the degree of compression of SBT and the temperature of SBT in the welding zone, which are constantly changing and can lead to problems during actual surgical welding. The use of thermocouples has its difficulties. Materials and methods. In this study, a neural network (NN) was proposed and investigated, developed using the Neural Network Toolbox program in MatLab. For training this neural network, data obtained as a result of modelling the welding process of biological tissue of a pig's heart in the COMSOL environment were used. The modelling took into account thermal processes and the compression force of the biological tissue. Results. It is crucial to have information about the thermal level of microbiological thermo compensation at given points to optimize the biological tissue welding process. This task can be effectively solved using artificial neural networks, which offer higher speed and accuracy compared to traditional methods. In this case, the neural network should be trained on an adequate model obtained by the finite element method or based on data from a physical experiment. The application of such a trained neural network allows taking into account the temperature and degree of compression of microbiological tissue by electrodes in the welding zone. In addition, the neural network can be used in a feedback system to control the technological process in order to ensure the necessary quality of welding. Conclusions. The article describes examples of approaches to creating a «virtual temperature sensor» between the electrodes in the biological tissue welding zone.